Copper induced cytosolic escape of mitochondrial DNA and activation of cGAS-STING-NLRP3 pathway-dependent pyroptosis in C8-D1A cells - Wei Shi; Qian Zhou; Lu Lu; Ying Zhang; Hu Zhang; Yuepu Pu; Lihong Yin (Ecotoxicology and Environmental Safety)
Copper, a vital mineral nutrient, possesses redox qualities that make it both beneficial and toxic to organisms. Excessive environmental copper exposure can result in neurological damage and cognitive decline in humans. Astrocytes, the predominant glial cells in the brain, are particularly vulnerable to pollutants, but the mechanism of copper-induced damage to astrocytes remains elusive. The aim of this study was to determine the role of the cyclic GMP-AMP synthase-stimulator of interferon genes (cGAS-STING) pathway in initiating NLRP3 inflammasome-induced astrocyte pyroptosis and chronic inflammation under conditions of copper overload. Our findings indicated that copper exposure elevated mitochondrial ROS (mtROS) levels, resulting in mitochondrial damage in astrocytes. This damage caused the release of mitochondrial DNA (mtDNA) into the cytoplasm, which subsequently activated the cGAS-STING pathway. This activation resulted in interactions between STING and NLRP3 proteins, facilitating the assembly of the NLRP3 inflammasome and inducing pyroptosis. Furthermore, depletion of mtROS mitigated copper-induced mitochondrial damage in astrocytes and reduced mtDNA leakage. Pharmacological inhibition of STING or STING transfection further reversed copper-induced pyroptosis and the inflammatory response. In conclusion, this study demonstrated that the leakage of mtDNA into the cytoplasm and the subsequent activation of the cGAS-STING-NLRP3 pathway may be potential mechanisms underlying copper-induced pyroptosis in astrocytes. These findings provided new insights into the toxicity of copper.